Virological responses to lamivudine or emtricitabine when combined with tenofovir and a protease inhibitor in treatment‐naïve HIV‐1‐infected patients in the Dutch AIDS Therapy Evaluation in the Netherlands (ATHENA) cohort. Issue 8 (4th February 2016) - Rokx, C; Gras, L; van de Vijver, DAMC; Verbon, A; Rijnders, BJA
Abstract : Objectives: Lamivudine (3TC) and emtricitabine (FTC) are considered interchangeable in recommended tenofovir disoproxil‐fumarate (TDF)‐containing combination antiretroviral therapies (cARTs). This statement of equivalence has not been systematically studied. We compared the treatment responses to 3TC and FTC combined with TDF in boosted protease inhibitor (PI)‐based cART for HIV‐1‐infected patients. Methods: An observational study in the AIDS Therapy Evaluation in the Netherlands (ATHENA) cohort was carried out between 2002 and 2013. Virological failure rates, time to HIV RNA suppression < 400 copies/mL, and time to treatment failure were analysed using multivariable logistic regression and Cox proportional hazard models. Sensitivity analyses included propensity score‐adjusted models. Results: A total of 1582 ART‐naïve HIV‐1‐infected patients initiated 3TC or FTC with TDF and ritonavir‐boosted darunavir (29.6%), atazanavir (41.5%), lopinavir (27.1%) or another PI (1.8%). Week 48 virological failure rates on 3TC and FTC were comparable (8.9% and 5.6%, respectively; P = 0.208). The multivariable adjusted odds ratio of virological failure when using 3TC instead of FTC with TDF in PI‐based cART was 0.75 [95% confidence interval (CI) 0.32–1.79; P = 0.51]. Propensity score‐adjusted models showed comparable results. The adjusted hazard ratio (HR) for treatment failure of 3TC compared with FTC was 1.15 (95% CI 0.58–2.27) within 240 weeks after cART initiation. The time to two consecutive HIV RNA measurements < 400 copies/mL within 48 weeks (HR 0.94; 95% CI 0.78–1.16) and the time to treatment failure after suppression < 400 copies/mL (HR 0.94; 95% CI 0.36–2.50) were not significantly influenced by the use of 3TC in TDF/PI‐containing cART. Conclusions: The virological responses were not significantly different in treatment‐naïve HIV‐1‐infected patients starting either 3TC/TDF or FTC/TDF and a ritonavir‐boosted PI.